2013
DOI: 10.1002/wcc.208
|View full text |Cite
|
Sign up to set email alerts
|

Carbon markets: a historical overview

Abstract: The global carbon trade has in a short space of time grown into a market worth over $175 billion a year. The history of carbon markets is a great political success story, and today they form an integral part of international climate change policy. Yet we only have a very limited understanding of how well these markets work in practice. Studying the incoming evidence and piecing it together with past emissions trading experiences can teach us a lot about how carbon markets work, and how they can fail. This arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 59 publications
0
36
0
5
Order By: Relevance
“…11 "Notice of carrying out carbon emissions trading pilot work"(Beijing) 2013. 12 "Guangdong carbon emission quota allocation and program of work for the first time (Trial)" 2013. 12 "Tianjin carbon trade management Interim Measures" 2014.…”
Section: Absence Of a Functional Carbon-trading Marketmentioning
confidence: 99%
See 3 more Smart Citations
“…11 "Notice of carrying out carbon emissions trading pilot work"(Beijing) 2013. 12 "Guangdong carbon emission quota allocation and program of work for the first time (Trial)" 2013. 12 "Tianjin carbon trade management Interim Measures" 2014.…”
Section: Absence Of a Functional Carbon-trading Marketmentioning
confidence: 99%
“…However, the international carbon-trading market has enormous room for growth. Calel [12] concluded that the global carbon trade could quickly grow into a market worth over $175 billion a year. Calel [12] noted how carbon markets work and how they can fail by studying incoming evidence and piecing it together with past emissionstrading experiences.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relevant literature has been identified through a strategic snowballing approach, starting out with articles providing a meta analysis of the impacts and effects of the EU ETS (Laing et al 2014;Calel 2013;Branger et al 2013;Venmans 2012;Wråke et al 2012;Bailey 2010;Convery 2009;Clò 2009). In order to cover also the more specific aspects of our analysis, this was complemented with parameterized snowballing from three additional reference points: innovation (Borghesi et al 2015;Schmidt et al 2012;Kemp and Pontoglio 2011), investments (Jong, Couwenberg, and Woerdman 2014;Löfgren et al 2013;Grubb 2012), institutions (Voß and Simons 2014;Hildén 2014;LaBelle 2012), and integration (Lehmann and Gawel 2013;Schlomann and Eichhammer 2014;Gawel, Strunz, and Lehmann 2014).…”
Section: Methodology and Materialsmentioning
confidence: 99%